What is manhood? : the significance of traditional circumcision in the Xhosa initiation ritual - Mhlahlo, Andile P. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2009.